MOLECULAR DETECTION OF STAPHYLOCOCCUS AUREUS ISOLATED FROM RAW MILK SAMPLES WITH COW MASTITIS - Sabrin. I. Mohsin , Sabrin. I. Mohsin; Aida .B. Allawe , Aida .B. Allawe (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Staphylococcus aureus is among the bacterial pathogens responsible for the global occurrence of cow mastitis. This study used the Vitek II system, morphological, cultural, biochemical, and identification of SpA and rpoA genes by polymerase chain reaction (PCR) to isolate and identify pathogenic bacteria S. aureus from raw milk samples. The study included collecting fifty milk samples from mastitis-affected cows from various sites within the Baghdad governorate included:(Abu Ghraib,Mahmudiyah and Radwaniyah) .The samples were streaked on a plate of Mannitol Salt Agar (MSA) to detect the presence of S. aureus, and the plates were then incubated at 37°C for a whole day. 12 out of 50 samples tested positive for S. aureus, according to the data. The results showed the isolates had the highest resistance rate (100%) to Benzylpenicillin, Amoxicillin , Ampicillin/SulbactamPiperacillin/Tazobactam , Cloxacillin ,Oxacillin, Azithromycin ,Clarithromycin, Erythromycin , and Clindamycin, and showed the prevalence of antimicrobial sensitivity to Ciprofloxacin , Moxifloxacin , Norfloxacin, Linezolid Teicoplanin, Vancomycin, Rifampicin, Trimethoprim/ Sulfamethoxazole. The SpA sequence analysis demonstrated 99% and 100% identity of the samples, confirming the results of the biochemical and culture characterisation. Additionally, the SpA and rpoA genes were present in all isolates.